Identifying common grounds for safety and security research: a comparative scientometric analysis focusing on development patterns, similarities, and differences - Li, Jie; Goerlandt, Floris; van Nunen, Karolien; Reniers, Genserik (Journal of Integrated Security and Safety Science, 2021)
Safety and security are often considered in complimentary or opposing terms. Discussions on their conceptual meaning have been put forward, and calls for an increased integration of these domains have been made. Nevertheless, there is currently no high-level empirical comparison of the development and contents of these research domains. In this article, the broad scientific literature of safety and security research obtained from Web of Science is analysed, aiming to obtain comparative insights in these respective fields, with a specific focus on the themes, topics and scientific areas where increased integration can be fruitful. Scientific publications are analysed in terms of research trends and geographic distribution, journals’ distribution, scientific categories, and focus topics of safety and security research in 2019. The results indicate a rapidly growing publication trend in both research domains, with an exponential growth since the 1990s. Safety research focuses on medicine/drug safety, patient safety and disease-related safety, with occupational health and safety and safety in socio-technical systems comparatively smaller research domains. Security research focuses on internet of things, physical layer security and cybersecurity/information security. Journals and scientific categories where significant contributions to both safety and security research are made relate mostly to industrial and transport safety and security, food safety, and public, environmental and occupational health. Apart from providing insights to academics and practitioners to the scope and focus areas of safety and security research, the findings also support delineating the scope and focus of the Journal of Integrated Security and Safety Science (JISSS), which aims to bolster connections and integration between these domains. Based on the findings, a focus on safety and security in industrial plants, transportation contexts, and industrially relevant aspects of public, environmental and occupational health, is found to be an appropriate target area for JISSS.